Switching from brittle to ductile isotactic polypropylene-g-maleic anhydride by crosslinking with capped-end polyether diamine. (15th February 2019) - Létoffé, Adrien; García-Rodríguez, Santiago M.; Hoppe, Sandrine; Canilho, Nadia; Godard, Olivier; Pasc, Andreea; Royaud, Isabelle; Ponçot, Marc
Abstract: Ductile functionalized polypropylene is of great interest in multi-layer composites development. A capped-end triblock polyether diamine (H2 N-PO2 -TMO9 -PO3 -NH2 ) was used as a linker of two different maleated isotactic polypropylenes (iPP -g- MAH, at 1 and 3 wt%) by twin-screw reactive extrusion. The molecular architecture, the semi-crystalline microstructure and the mechanical properties of the resulting polymers were analysed as a function of the molar ratio of NH2 :MAH (0:1, 0.33:1, 0.5:1, 0.66:1, 1:1, 1.5:1, 2:1). At the molecular scale, the chemically modified polymers were characterized by FTIR and by the determination of gel content following the ASTM D2765-84 standard method. Differential Scanning Calorimetry, Wide Angle X-rays Scattering and Self Successive Auto-nucleation techniques showed the impact of the crosslinking: a decrease of the melting temperature as compared with the unmodified iPP -g- MAH polymer, as well as a decrease of the crystallinity ratio for the iPP -g- MAH at 3 wt% of MAH. Interestingly, Dynamic Mechanical Analysis and video-controlled uniaxial tensile tests showed that the polymers obtained in stoichiometric NH2 :MAH molar ratio exhibit the best mechanical properties enlightened by a switch from brittle to ductile mechanical behaviour with few differences between the two iPP -g- MAH. Graphical abstract: A slight crosslinking enables maleated isotactic polypropylenes to switch from brittle to ductile mechanical behavior with higher resilience than the most conventional one.Image 1 Highlights: A capped-end triblock polyetherdiamine is used as a linker of different iPP- g -MAH by twin-screw reactive extrusion. The three-dimensional networks are characterized by FTIR and by the determination of gel content. The semi-crystalline microstructure is thermally described applying the Self-Successive Auto nucleation technique. A switch from brittle to ductile mechanical properties is observed studying the intrinsic true mechanical behaviours.